Quality parameters and shelf-life of smoked Dalmatian dry-cured ham packed in bio-based and plastic bilayer pouches. (December 2021) - Kurek, Mia; Poljanec, Ivna; Marušić Radovčić, Nives; Galić, Kata; Medić, Helga
Abstract: Traditional Dalmatian dry-cured ham (prosciutto) was packaged under modified atmosphere, MAP (30%CO2 /70%N2 ) and vacuum, in commercial polyamide/polyethylene (PA/PE) and biodegradable poly(lactic acid) (PLA) material. Samples were stored at 4 °C for 180 days and the effect of packaging materials and methods on various quality parameters was studied. The least changes were observed for PA/PE for both packaging methods. The pH, moisture content, colour parameters, TBARS and DNPH values of dry-cured ham packed in PLA were significantly affected already after 1 month in MAP and after 3 months in vacuum packaging. Similar changes in the above parameters were also observed in the control sample (packed in air-PA/PE) while vacuum-PA/PE and MAP-PA/PE showed significantly better results. The instrumental analyses agreed with the sensory panel results where appearance, taste, texture and overall acceptability of PLA samples decreased significantly already after 2 months of storage. For both, MAP-PA/PE and vacuum-PA/PE samples, the shelf-life was estimated to be 5 months. Graphical abstract: Image 1 Highlights: Dry-cured Dalmatian ham was packed in MAP and under vacuum in PLA and PA/PE. The permeability of the materials played an important role in determining the end of shelf-life. MAP-PLA showed significantly increased lipid and protein oxidation already after 1 month, while vacuum-PLA after 3 months. Samples packed in vacuum were more stable than samples in MAP. PLA could be suitable for short-term storage of dry-cured ham.